Petrogenesis of high-grade metamorphic soles from the Central Dinaric Ophiolite belt and their significance for the Neotethyan evolution in the Dinarides - Šegvić, Branimir; Altherr, Rainer (Ofioliti, 2019)
High-grade metamorphic soles in NE Bosnia and Herzegovina make part of the Krivaja-Konjuh ophiolite complex (KKOC), which is one of the most important constituents of the Jurassic ophiolite mélange of the Central Dinarides. Several rock types were distinguished within the investigated metamorphic suite - sapphirine and corundum amphibolites, garnet-clinopyroxene±orthopyroxene amphibolites, clinopyroxene±garnet amphibolites, amphibolites per se and clinopyroxene+plagoclase±garnet gneisses.Peak temperature and pressure conditions calculated from different mineral pairs were estimated to range between 850 and 1100°C at 1.1 to 1.3 GPa. A prograde multi-stage metamorphic history of analyzed rocks was followed by the post-peak relaxation witnessed in decomposing porphyroblasts of garnet and ubiquitous formation of amphibole and orthopyroxene rims around clinopyroxene. The whole-rock chemical composition of magmatic protoliths largely defines it as cumulates from supra-subduction zones and scarcely as MORB-like tholeiitic mafic extrusives. Their origin is linked to near-ridge crust generation of a back-arc basin. Following the Middle Jurassic contraction of Neotethyan a portion of these rocks was likely entrained in an incipient subduction/thrusting system characteristic for the formation of metamorphic soles. According to geological evidences, and most notably, the age of radiolarians taken from KKOC basalts, the formation of metamorphic sole rocks must have followed a rapid transition in the Dinaridic Neotethys geotectonic setting before its final obduction onto the Adria margins in the next 15 Ma before the end of Jurassic.
Gesehen am 22.07.2019